1992
DOI: 10.1002/jccs.199200101
|View full text |Cite
|
Sign up to set email alerts
|

Chemosystematic Correlations of Taiwanese Hepaticae

Abstract: Significance from the chemotaxonomic viewpoint is discussed on the basis of previous studies and recent findings on the chemical constituents of Taiwanese liverworts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…6 However, as all studies were carried out on Japanese species, we were interested to know whether there is any chemical difference among species from other areas since it has been shown that different chemotypes do exist in some liverwort species. [7][8][9] Our results…”
Section: Introductionmentioning
confidence: 90%
“…6 However, as all studies were carried out on Japanese species, we were interested to know whether there is any chemical difference among species from other areas since it has been shown that different chemotypes do exist in some liverwort species. [7][8][9] Our results…”
Section: Introductionmentioning
confidence: 90%
“…The compounds we were able to tentatively identify were terpene-related. Apart from (+)-cyclosativene they are known to be produced by other mosses or liverworts [49][50][51][52][53] . Consequently, if the VOCs blend carried information about the genetic identity of S. flexuosum and the information was encoded by VOCs detected in our study, the key part of the cue could be (+)-cyclosativene, one of the unidentified compounds or a specific combination and/or concentration of the detected chemicals.…”
Section: H Vernicosus Changes Growth and Vocs Emission In Response Tmentioning
confidence: 99%
“…R. hemisphaerica and Mannia subpilosa produce marchantia quinone (26) [34,44]. Marchantin O (24), the monomethyl ether of marchantin C (10), and marchantin P (25) were obtained from R. hemisphaerica [44,46,47] and South American Marchantia chenopoda, respectively [37]. Their structures have been elucidated by analysis of the spectral data including difference NOE of the permethylated and the peracetylated derivatives.…”
Section: Structures Of Cyclic Bis(bibenzyls)mentioning
confidence: 99%